ALASAN TIONGKOK MENGHENTIKAN IMPOR SAMPAH PLASTIK POLIETILENA TEREFTALAT (PET) TAHUN 2018 - Bharata W, A.A Gede Agung; Dharmiasih, D.A Wiwik; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABS TRACT   T his paper s eeks to explain the r eason behind China’s decision t o ban p l astic waste i m port i n 2018. China’s i mport on p l astic waste were i ncreasing s i gnificantly s i nce 200 W i thin ten y ear s i nce 2006, China  i mported  half  of  world’s   plastic   waste.  China’s   r ecycling  i ndustry   turned plastic waste i nto sy nthetic fiber c a ll e d polyester. H o wever, s i nce 2 018 China d ecided t o b an plastic waste i mport. T his  r esearch i s analyzed using qualitative r esearch methodology with s econdary data c ollection f ocusing o n s tate l evel analysis. T his paper r efers to two c onceptual frameworks, which are r ational c hoice actor and environmental s ecurity. T he f i n dings on this r esearch l eads t o a c onclusion t hat explains China’s decision i s based on i ts profit c alculation from textile i ndustry and p l a s tic waste r ecycling.   Key  wo r d s:  P l astic  w aste,  r ational  actor  c hoice,  e nvironmental  problem,  a nd  health  i ss ue .